Preparation method of graphene reinforced copper composite material
Through liquid phase catalytic technology and in-situ growth strategy, graphene is grown on the copper powder surface, and discharge plasma sintering treatment, the shortcomings of traditional copper-based composite materials in high temperature stability, yield strength and electric and thermal conductivity are solved, and the high-performance preparation of graphene-reinforced copper composite materials is achieved.
Patent Information
- Application Number
- CN202510040790.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Traditional copper-based composite materials have shortcomings in high temperature stability, yield strength and electric and thermal conduction properties, and are difficult to meet the application needs of emerging industries.
Using liquid phase catalytic technology and in-situ growth strategy, graphene is grown in situ on the copper powder surface at relatively low temperatures to form a uniform and complete graphene cladding layer, and then graphene reinforced copper composite material is prepared by discharge plasma sintering treatment.
The tensile strength, elongation of fracture, conductivity and thermal diffusion coefficient of composite materials are significantly improved, and the comprehensive performance is better than that of pure copper, and the process is simple and easy to produce.
Smart Images

Figure CN119819926A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and particularly relates to a method for preparing a graphene-reinforced copper composite material. Background Art
[0002] Traditional pure copper materials are widely used in aerospace, low-voltage electrical appliances, communication transmission and other fields due to their high electrical conductivity, thermal conductivity and high ductility. However, due to their poor high-temperature stability and low yield strength, they cannot meet the application needs of emerging industries that are developing rapidly in today's society. Although traditional copper alloys have improved their yield strength, they have lost a lot of electrical and thermal conduction functionality due to the strong carrier scattering of alloy elements. Copper-based composite materials fully combine the excellent properties of the reinforcing phase with high electrical and thermal conductivity with the copper matrix to achieve a synergistic improvement in comprehensive properties such as electrical conductivity, thermal conductivity and mechanics.
[0003] Currently, the nanocarbon reinforcement phases that have received widespread attention include carbon nanotubes, graphene, etc. By introducing the nanocarbon reinforcement phase into the copper matrix and combining the advantages of the copper matrix and nanocarbon, the single or comprehensive properties of the copper-based composite material, such as strength, oxidation resistance, high temperature stability and wear resistance, can be significantly improved, and it has broad application prospects. In view of the excellent inherent properties of graphene and its synergistic effect with copper, graphene / copper composite materials are expected to develop into advanced composite material systems with high electrical conductivity and thermal conductivity. At present, one of the main means of preparing such composite materials is to mix graphene into copper powder by external addition and ball milling. However, this method faces problems such as insufficient interface wettability between graphene and copper matrix, low interface bonding strength, uneven distribution of graphene and easy agglomeration.
[0004] The present invention uses liquid phase catalytic technology and an in-situ growth strategy to achieve in-situ growth of graphene on the surface of copper powder under relatively low temperature conditions, thereby achieving uniform and complete wrapping of copper powder by graphene, significantly improving the problems encountered in the traditional addition method preparation process. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for preparing a graphene-reinforced copper composite material.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a graphene-reinforced copper composite material, comprising:
[0008] (1) reducing the copper powder in a reducing gas to obtain reduced copper powder;
[0009] (2) mixing the nano-carbon material suspension and the reduced copper powder, and freeze-drying the mixture to obtain a mixed powder;
[0010] (3) feeding the mixed powder into a tube furnace at room temperature, setting growth conditions, and performing in-situ growth of graphene on the surface of the copper powder, and cooling the furnace to room temperature after the growth is completed to obtain a graphene / copper composite powder;
[0011] The in-situ growth conditions include: closing the furnace tube, pumping out the residual air in the furnace, introducing 100-200 sccm of argon and 10-50 sccm of hydrogen, and starting to uniformly heat to 300° C. in stages at room temperature and keeping the temperature for 50-70 minutes; then uniformly heating to 500-800° C., introducing argon at a flow rate of 5-20 sccm, keeping the temperature for 50-70 minutes for in-situ growth; and then cooling to room temperature;
[0012] (4) The graphene / copper composite powder is subjected to spark plasma sintering to obtain a graphene reinforced copper composite material.
[0013] The present invention adopts a staged in-situ growth method, which can ensure a good Cu-C interface on the one hand, is conducive to improving the load transfer capacity and continuous propagation, and improving the electrical conductivity and thermal diffusion coefficient of the composite material. On the other hand, in the in-situ growth stage, by heating and heat preservation in sections and changing the ventilation flow rate at the same time, the quality of the in-situ grown graphene is further improved, ensuring that high-quality graphene is generated at a low temperature, and the crystallinity of the graphene is good, which is conducive to improving the tensile strength, elongation at break, electrical conductivity and thermal diffusion coefficient of the material.
[0014] As a preferred embodiment of the present invention, the nano carbon material has sp 2 Hybrid structured nanocarbon materials, including but not limited to carbon quantum dots. 2 Hybrid structured nanocarbon materials are mainly composed of sp 2 Hybridized carbon atoms are composed in the form of a hexagonal network. The chemical structure of CQDs carbon quantum dots is mainly composed of a well-crystalline sp2 carbon core and surface groups.
[0015] The present invention adopts a sp 2 The hybrid structured nanocarbon material suspension is used as the carbon source, and iodine tincture can uniformly adsorb the carbon source and nucleation sites on the surface of the copper powder with a complex microstructure. Moreover, iodine tincture as a catalyst can in situ grow high-quality graphene on the surface of the copper powder at low temperature, and promote the bonding of graphene to form a large network, thereby preparing a graphene-reinforced copper composite material with uniform coating and good structure.
[0016] As a preferred embodiment of the present invention, in step (1), the reduction temperature is 300°C, the holding time is 250-360 minutes, the argon flow rate during reduction is 100-200 sccm, and the hydrogen flow rate is 10-40 sccm. Pre-reduction of copper powder can remove impurities such as oxides, which is beneficial to the coating of the carbon source.
[0017] As a preferred embodiment of the present invention, the method for preparing the nano carbon material suspension comprises: 2 The carbon quantum dots with hybrid structure are ultrasonically dispersed in a mixed solution of ethanol, water and iodine to obtain a carbon quantum dot suspension.
[0018] The sp 2 The hybrid structured carbon quantum dots are commercially available products, which are fluorescent green carbon quantum dots. The fluorescent green carbon quantum dots have very few residual impurities during the preparation process, the carbon source is of high purity, and the particle size is 2-5 nm.
[0019] As a preferred embodiment of the present invention, the volume ratio of ethanol, water and iodine tincture is (5-10): (10-20): (0.01-0.05).
[0020] As a preferred embodiment of the present invention, in the step (3), the mass of carbon quantum dots in the nano-carbon material suspension accounts for 0.01%-0.2% of the mass of the copper powder; and the average particle diameter of the copper powder is 1-20 μm.
[0021] As a preferred embodiment of the present invention, the nano-carbon material suspension and the copper powder are stirred and mixed at a speed of 100-200 rpm for 6-12 hours. By combining the solution stirring method with freeze drying, the carbon source can be evenly coated on the surface of the copper powder, and freeze drying will not cause the loss of the carbon source, so the present invention can clearly define the content of the added carbon source.
[0022] As a preferred embodiment of the present invention, the spark plasma sintering temperature is 650-750° C., the vacuum degree is lower than 5 Pa, the heating rate is 50-150° C. / min, and the holding time is 10-30 min.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The invention adopts highly active carbon quantum dots, dissolves them in a solution, ultrasonicates them, activates them, adds iodine and copper powder to stir them evenly, freeze-dries them, and uniformly adsorbs carbon sources and nucleation sites on the surface of the copper powder with a complex microstructure. Then, graphene is grown in situ at a low temperature by iodine catalysis to prepare a graphene / copper composite powder with good coating, uniform structure and tight bonding. Then, a graphene-reinforced copper composite material with a continuous structure and strong interface bonding is prepared by sintering. The large specific surface area graphene with uniform coating is used to improve the carrier and load transfer capacity of the composite material, which is beneficial to the transmission of electricity, heat and force, so that the electrical conductivity of the composite material is as high as 90-100.8% IACS, the tensile strength reaches 207-263MPa, and the thermal diffusion coefficient reaches 101.8-120.8mm 2 / s, the comprehensive performance is better than that of pure copper, and the method is simple in process and easy to produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The SEM morphology images of the graphene / copper composite powder prepared in step (3) of Examples 1-4, wherein a is Example 1, b is Example 2, c is Example 4, and d is Example 5.
[0026] Figure 2 This is the Raman spectrum of the graphene / copper composite powder prepared in step (3) of Example 1-4.
[0027] Figure 3 TEM images of the graphene coating layer of the graphene / copper composite powder prepared in step (3) of Examples 3 and 4 after dissolving copper, the left image is Example 3, and the right image is Example 4.
[0028] Figure 4 The left figure is the SEM morphology image of the pure copper powder prepared in Comparative Example 1, and the right figure is the SEM morphology image of the graphene / copper composite powder prepared in step (3) of Comparative Example 2. DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0030] Example 1
[0031] A method for preparing a graphene-reinforced copper composite material, comprising the following specific steps:
[0032] (1) 10 g of copper powder (average particle diameter is about 20 μm) was kept at a reduction temperature of 300°C for 250 min, with an argon flow rate of 100 sccm and a hydrogen flow rate of 10 sccm. The heating time was 40 min. The copper powder was reduced in advance to remove impurities such as oxides, which is beneficial to the coating of the carbon source.
[0033] (2) 2.5 mg of carbon quantum dots were ultrasonically dispersed in a mixed solution of 5 ml of anhydrous ethanol, 15 ml of deionized water and 0.01 ml of iodine tincture to obtain a carbon quantum dot having sp 2 The nanocarbon material suspension with hybrid structure is then 2 The hybrid structure nano-carbon material suspension was stirred and mixed with 10 g of copper powder obtained in step (1), and freeze-dried at a stirring speed of 200 rpm for 6 hours to obtain a precursor powder with a surface coated with a carbon source, wherein the mass of the added carbon quantum dots was 0.025% of the mass of the copper powder.
[0034] (3) The precursor powder obtained in step (2) is placed in a tubular furnace to grow graphene in situ, wherein the first reduction stage has a heating time of 30 minutes, a heat preservation time of 50 minutes, a temperature of 300°C, an argon flow rate of 190 sccm, and a hydrogen flow rate of 10 sccm. The second growth stage has a heating time of 30 minutes, a heat preservation time of 50 minutes, a growth temperature of 500°C, and an argon flow rate of 5 sccm to obtain a graphene / copper composite powder. Through segmented heating and heat preservation, the copper powder is reduced to a certain extent in the first heat preservation stage to remove the influence of impurities such as oxides on the growth quality of graphene, and at the same time, the gas flow rate is changed at the in-situ growth temperature, thereby further improving the quality of the in-situ grown graphene.
[0035] (4) The composite powder obtained in step (3) is subjected to spark plasma sintering to obtain a graphene / copper composite material. The spark plasma sintering is performed at a temperature of 650° C., a vacuum degree of less than 5 Pa, a heating rate of 70° C. / min, and a holding time of 10 min to obtain a graphene-reinforced copper composite material.
[0036] The microscopic morphology of the graphene / copper composite powder obtained in step (3) of this embodiment is as follows: Figure 1 As shown in a, graphene is uniformly grown and coated on the surface of the copper powder, but it can be seen that the graphene is partially broken and discontinuous, making it difficult to form a continuous propagation path for carriers and loads.
[0037] After spark plasma sintering, the mechanical properties test showed that the tensile strength of the graphene-enhanced copper composite material under this process condition was 210MPa, the elongation at break was 34.8%, the electrical properties test showed that the conductivity of the graphene-enhanced copper composite material was 100.8% IACS, and the thermal properties test showed that the thermal diffusion coefficient was 107mm 2 / s.
[0038] Example 2
[0039] A method for preparing a graphene-reinforced copper composite material, comprising the following specific steps:
[0040] (1) 10 g of copper powder (average particle diameter of about 20 μm) was kept at a reduction temperature of 300°C for 300 min, with an argon flow rate of 150 sccm and a hydrogen flow rate of 20 sccm. The heating time was 40 min. The copper powder was reduced in advance to remove impurities such as oxides, which was beneficial to the coating of the carbon source.
[0041] (2) 5 mg of carbon quantum dots were ultrasonically dispersed in a mixed solution of 7 ml of anhydrous ethanol, 15 ml of deionized water and 0.03 ml of iodine tincture to obtain 2 The nanocarbon material suspension with hybrid structure is then 2 The hybrid nanocarbon material suspension was stirred and mixed with 10 g of copper powder obtained in step (1), and freeze-dried at a stirring speed of 100 rpm for 12 hours to obtain a precursor powder with a surface coated with a carbon source, wherein the mass of the added carbon quantum dots was 0.05% of the mass of the copper powder.
[0042] (3) The precursor powder obtained in step (2) is placed in a tubular furnace to grow graphene in situ, wherein the first reduction stage is heated for 30 minutes, kept warm for 60 minutes, at a temperature of 300°C, with an argon flow rate of 190 sccm and a hydrogen flow rate of 20 sccm. The second growth stage is heated for 30 minutes, kept warm for 60 minutes, at a growth temperature of 600°C, with an argon flow rate of 20 sccm to obtain a graphene / copper composite powder.
[0043] (4) The composite powder obtained in step (3) is molded into a graphene / copper composite material by spark plasma sintering. The spark plasma sintering is performed at a temperature of 680° C., a vacuum degree of less than 5 Pa, a heating rate of 150° C. / min, and a holding time of 15 min to obtain a graphene-enhanced copper composite material.
[0044] The microscopic morphology of the graphene / copper composite powder obtained in step (3) of this embodiment is as follows: Figure 1 As shown in Figure b, graphene is grown and coated on the surface of copper powder, but there is still uncovered copper powder. At the same time, it can be seen that some graphene is in thicker layers, indicating that adding carbon source can grow more graphene under this process. After sintering, the mechanical properties test shows that the tensile strength of the graphene-enhanced copper composite material under this process condition is 225MPa, the elongation at break is 36.5%, the electrical properties test shows that the electrical conductivity of the composite material is 99.9% IACS, and the thermal properties test shows that the thermal diffusion coefficient is 112mm 2 / s.
[0045] Example 3
[0046] A method for preparing a graphene-reinforced copper composite material, comprising the following specific steps:
[0047] (1) 10 g of copper powder (average particle diameter of about 20 μm) was kept at a reduction temperature of 300°C for 360 min, with an argon flow rate of 180 sccm and a hydrogen flow rate of 20 sccm. The heating time was 40 min. The copper powder was reduced in advance to remove impurities such as oxides, which was beneficial to the coating of the carbon source.
[0048] (2) 7.5 mg of carbon quantum dots were ultrasonically dispersed in a mixed solution of 6 ml of anhydrous ethanol, 13 ml of deionized water, and 0.045 ml of iodine tincture to obtain a carbon quantum dot having sp 2 The nanocarbon material suspension with hybrid structure is then 2 The hybrid nanocarbon material suspension was stirred and mixed with 10 g of copper powder obtained in step (1), and freeze-dried at a stirring speed of 150 rpm for 10 hours to obtain a precursor powder with a surface coated with a carbon source, wherein the mass of the added carbon quantum dots was 0.075% of the mass of the copper powder.
[0049] (3) The precursor powder obtained in step (2) is placed in a tubular furnace to grow graphene in situ, wherein the first reduction stage has a heating time of 30 minutes, a heat preservation time of 60 minutes, a temperature of 300°C, an argon flow rate of 180 sccm, and a hydrogen flow rate of 20 sccm. The second growth stage has a heating time of 30 minutes, a heat preservation time of 60 minutes, a growth temperature of 630°C, an argon flow rate of 10 sccm, and a graphene / copper composite powder is obtained. Through segmented heating and heat preservation, the copper powder is reduced to a certain extent in the first heat preservation stage to remove the influence of impurities such as oxides on the growth quality of graphene, and at the same time, the gas flow rate introduced is changed at the in-situ growth temperature, reducing the adverse effect of excessive gas flow on graphene growth during in-situ growth, and further improving the quality of graphene grown in situ.
[0050] (4) The graphene / copper composite powder obtained in step (3) is molded by spark plasma sintering to obtain a graphene / copper composite material. The spark plasma sintering is performed at a temperature of 700° C., a vacuum degree of less than 5 Pa, a heating rate of 100° C. / min, and a holding time of 10 min to obtain a graphene-enhanced copper composite material.
[0051] The microscopic morphology of the graphene / copper composite powder obtained in step (3) of this embodiment is as follows: Figure 1 As shown in Fig. 3, graphene is uniformly grown and coated on the surface of the copper powder. Combined with the TEM analysis of the graphene coating layer after the copper is dissolved in the graphene / copper composite powder obtained in step (3), it can be seen that Figure 3 (Left picture) In the process of this embodiment, a continuous, uniform, large-sized graphene coating layer is obtained, which can effectively transfer the load and form a continuous carrier migration path.
[0052] After sintering, the mechanical properties test showed that under this process, the tensile strength of the graphene-enhanced copper composite material was 240MPa, the elongation at break was 31.5%, and the tight interface bonding between the surface graphene and copper effectively improved the load transfer capacity and facilitated the continuous propagation of carriers. The electrical properties test showed that the conductivity of the graphene-enhanced copper composite material was 99.6% IACS, and the thermal properties test showed that the thermal diffusion coefficient was 114mm 2 / s.
[0053] Example 4
[0054] The preparation method of the graphene-enhanced copper composite material in this embodiment is different from that in Embodiment 3 in that:
[0055] The amount of carbon quantum dots added in step (2) is 9 mg, which is 0.09% of the mass of the copper powder.
[0056] The microscopic morphology of the graphene / copper composite powder obtained in step (3) of this embodiment is as follows: Figure 1 As shown in FIG. d, combined with the TEM analysis of the graphene coating layer after the copper is dissolved in the composite powder obtained in step (3), it can be seen that Figure 3 (Right) A more continuous and larger uniform graphene coating layer is generated on the surface of the copper powder. After sintering, a continuous graphene structure can be formed inside the composite material. Raman detection shows that the degree of defects in the graphene is not high. Figure 2 .
[0057] The mechanical properties test shows that under this process condition, the tensile strength of the graphene-enhanced copper composite material is 253MPa, the elongation at break is 29.5%, the electrical properties test shows that the conductivity of the graphene-enhanced copper composite material is 98.2%IACS, and the thermal properties test shows that the thermal diffusion coefficient is 118mm 2 / s.
[0058] Example 5
[0059] A method for preparing a graphene-reinforced copper composite material, comprising the following specific steps:
[0060] (1) 10 g of copper powder (average particle diameter of about 20 μm) was kept at a reduction temperature of 300°C for 360 min, with an argon flow rate of 200 sccm and a hydrogen flow rate of 40 sccm. The heating time was 40 min. The copper powder was reduced in advance to remove impurities such as oxides, which was beneficial to the coating of the carbon source.
[0061] (2) 20 mg of carbon quantum dots were placed in a mixed solution of 10 ml of anhydrous ethanol, 20 ml of deionized water, and 0.05 ml of iodine tincture for ultrasonic dispersion to obtain a carbon quantum dot having sp 2 The nanocarbon material suspension with hybrid structure is then 2 The hybrid nanocarbon material suspension was mixed with 10 g of copper powder obtained in step (1) and freeze-dried at a stirring speed of 150 rpm for 10 h to obtain a precursor powder with a surface coated carbon source, wherein the mass of the added carbon quantum dots was 0.2% of the mass of the copper powder.
[0062] (3) The precursor powder obtained in step (2) is placed in a tubular furnace to grow graphene in situ, wherein the first reduction stage has a heating time of 30 minutes, a heat preservation time of 70 minutes, a temperature of 300°C, an argon flow rate of 100 sccm, and a hydrogen flow rate of 50 sccm. The second growth stage has a heating time of 30 minutes, a heat preservation time of 70 minutes, a growth temperature of 800°C, an argon flow rate of 20 sccm, and a graphene / copper composite powder is obtained. Through segmented heating and heat preservation, the copper powder is reduced to a certain extent in the first heat preservation stage, and the influence of impurities such as oxides on the growth quality of graphene is removed. At the same time, the gas flow rate introduced is changed at the in-situ growth temperature, and the adverse effect of excessive gas flow on the growth of graphene during in-situ growth is reduced, thereby further improving the quality of graphene grown in situ.
[0063] (4) The composite powder obtained in step (3) is molded into a graphene / copper composite material by spark plasma sintering. The spark plasma sintering is performed at a temperature of 750° C., a vacuum degree of less than 5 Pa, a heating rate of 50° C. / min, and a holding time of 30 min to obtain a graphene-enhanced copper composite material.
[0064] The graphene / copper composite powder obtained in step (3) of this embodiment is a graphene coated on the surface of copper powder uniformly grown. In the process of this embodiment, a continuous, uniform, large-sized graphene coating layer is obtained, which can effectively transfer loads and form a continuous carrier migration path. After sintering and forming, the mechanical property test shows that the tensile strength of the graphene-enhanced copper composite material under this process condition is 263MPa, and the elongation at break is 30.5%. The tight interface bonding of the surface graphene-copper effectively improves the load transfer capacity and is conducive to the continuous propagation of carriers. The electrical performance test shows that the conductivity of the graphene-enhanced copper composite material is 98.9%IACS, and the thermal performance test shows that the thermal diffusion coefficient is 120.8mm2 / s.
[0065] Comparative Example 1
[0066] The only difference between the preparation method of the copper material described in this comparative example and that of Example 3 is that the reduction and subsequent coating of the carbon source and the in-situ growth process in steps (2) and (3) are not performed; only the copper powder is reduced in step (1), such as Figure 4 (Left picture), and then the pure copper block was prepared by spark plasma sintering molding process. The mechanical properties test showed that the tensile strength of the pure copper block under this process condition was 207MPa, the elongation at break was 45.5%, the electrical properties test showed that the material conductivity was 100.3IACS%, and the thermal properties test showed that the thermal diffusion coefficient was 101.8mm 2 / s.
[0067] Compared with the comparative example 1, the graphene-copper composite materials prepared in the examples of the present invention show that the tensile strength of the graphene-enhanced copper composite materials in Examples 1-5 is improved, and good elongation and electrical conductivity are maintained. At the same time, the thermal conductivity of the graphene-enhanced copper composite materials is improved compared with pure copper, indicating that the preparation method proposed in the present invention is conducive to improving the comprehensive performance of pure copper-based composite materials.
[0068] Comparative Example 2
[0069] The difference between the preparation method of the graphene-enhanced copper composite material described in this comparative example and that of Example 3 is that the average particle diameter of the copper powder reduced in step (1) is adjusted to 1 μm, and the amount of carbon quantum dots added in step (2) is adjusted to 0.5 mg.
[0070] In this comparative example, the particle diameter and morphology of the copper powder are changed, resulting in a change in the morphology and structure of the graphene coating layer grown in situ on the surface of the copper powder. Figure 4 (Right picture), graphene grows only partially on the surface of copper powder, and it is difficult to densify during the sintering process. It is difficult for graphene to form a continuous structure in the graphene / copper composite powder. The mechanical properties test shows that under this process condition, the tensile strength of the graphene-enhanced copper composite material is 215MPa, the elongation at break is 35.5%, the electrical properties test shows that the electrical conductivity of the composite material is 90% IACS, and the thermal properties test shows that the thermal diffusion coefficient is 104mm 2 / s.
[0071] Comparative Example 3
[0072] A method for preparing a graphene-reinforced copper composite material, comprising the following specific steps:
[0073] (1) 10 g of copper powder (average particle diameter of about 20 μm) was kept at a reduction temperature of 300°C for 360 min, with an argon flow rate of 180 sccm and a hydrogen flow rate of 20 sccm. The heating time was 40 min. The copper powder was reduced in advance to remove impurities such as oxides, which was beneficial to the coating of the carbon source.
[0074] (2) 7.5 mg of carbon quantum dots were placed in a mixed solution of 6 ml of anhydrous ethanol and 13 ml of deionized water and ultrasonically dispersed to obtain a carbon quantum dot having sp 2 The nanocarbon material suspension with hybrid structure is then 2 The hybrid nanocarbon material suspension was stirred and mixed with 10 g of copper powder obtained in step (1), and freeze-dried at a stirring speed of 150 rpm for 10 hours to obtain a precursor powder with a surface coated with a carbon source, wherein the mass of the added carbon quantum dots was 0.075% of the mass of the copper powder.
[0075] (3) The precursor powder obtained in step (2) is placed in a tubular furnace to grow graphene in situ, wherein the first reduction stage has a heating time of 30 minutes, a heat preservation time of 60 minutes, a temperature of 300°C, an argon flow rate of 180 sccm, and a hydrogen flow rate of 20 sccm. The second growth stage has a heating time of 30 minutes, a heat preservation time of 60 minutes, a growth temperature of 630°C, and an argon flow rate of 10 sccm to obtain a graphene / copper composite powder. Through segmented heating and heat preservation, the copper powder is reduced to a certain extent in the first heat preservation stage to remove the influence of impurities such as oxides on the growth quality of graphene, and at the same time, the gas flow rate introduced is changed at the in-situ growth temperature, reducing the adverse effect of excessive gas flow on graphene growth during in-situ growth, and further improving the quality of graphene grown in situ.
[0076] (4) Sintering the graphene / copper composite powder obtained in step (3) to obtain a graphene / copper composite material. Spark plasma sintering is adopted, the temperature is 700° C., the vacuum degree is lower than 5 Pa, the heating rate is 100° C. / min, and the holding time is controlled to be 10 min to obtain a graphene-reinforced copper composite material.
[0077] In this comparative example, since no iodine was added, the carbon source and nucleation sites were difficult to be adsorbed on the surface of the copper powder, so it was difficult to fully grow into graphene during the low-temperature growth stage, resulting in changes in the morphology and structure of the graphene coating grown in situ on the copper powder surface, making it difficult to partially grow graphene on the copper powder surface, still maintaining the original discontinuous carbon source structure, and difficult to densify during the sintering process. Mechanical property tests show that the tensile strength of the graphene-enhanced copper composite material under this process condition is 220MPa, and the elongation at break is 38.5%. The electrical property test shows that the electrical conductivity of the composite material is 94% IACS, and the thermal property test shows that the thermal diffusion coefficient is 103.5mm 2 / s.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a graphene-reinforced copper composite material, characterized in that: include: (1) reducing the copper powder in a reducing gas to obtain reduced copper powder; (2) mixing the nano-carbon material suspension and the reduced copper powder, and freeze-drying the mixture to obtain a mixed powder; (3) feeding the mixed powder into a tube furnace at room temperature, setting growth conditions, and performing in-situ growth of graphene on the surface of the copper powder, and cooling the furnace to room temperature after the growth is completed to obtain a graphene / copper composite powder; The growth conditions include: closing the furnace tube, pumping out the residual air in the furnace, introducing 100-200 sccm of argon and 10-50 sccm of hydrogen, heating at a constant speed to 300° C. at room temperature and keeping the temperature for 50-70 minutes; then heating at a constant speed to 500-800° C., introducing argon at a flow rate of 5-20 sccm, keeping the temperature for 50-70 minutes for in-situ growth; (4) The graphene / copper composite powder is subjected to spark plasma sintering to obtain a graphene reinforced copper composite material.
2. The method for preparing the graphene-enhanced copper composite material according to claim 1, characterized in that: In the step (1), the reduction temperature is 300° C. and the holding time is 250-360 min; the reducing gas is a mixture of hydrogen and argon, the argon flow rate is 100-200 sccm, and the hydrogen flow rate is 10-40 sccm.
3. The method for preparing the graphene-enhanced copper composite material according to claim 1, characterized in that: The preparation method of the nano-carbon material suspension comprises: placing carbon quantum dots in a mixed solution of ethanol, water and iodine for ultrasonic dispersion to obtain the carbon quantum dot suspension.
4. The method for preparing the graphene-enhanced copper composite material according to claim 1, characterized in that: The volume ratio of the ethanol, water and iodine tincture is (5-10):(10-20):(0.01-0.05).
5. The method for preparing the graphene-enhanced copper composite material according to claim 3, characterized in that: In the step (3), the mass of the carbon quantum dots in the nano-carbon material suspension accounts for 0.01%-0.2% of the mass of the reduced copper powder; and the average particle diameter of the copper powder is 1-20 μm.
6. The method for preparing the graphene-enhanced copper composite material according to claim 1, characterized in that: The nano-carbon material suspension and the copper powder are stirred and mixed at a rotation speed of 100-200 rpm for 6-12 hours.
7. The method for preparing the graphene-enhanced copper composite material according to claim 1, characterized in that: The spark plasma sintering temperature is 650-750° C., the vacuum degree is lower than 5 Pa, the heating rate is 50-150° C. / min, and the heat preservation time is 10-30 min.
Citation Information
Patent Citations
Method for preparing composite material by generating carbon dots on surface of copper powder in situ
CN115007852A
In-situ interface modification method of graphene-copper-based composite material
CN115522095A
Preparation method of in-situ growth graphene reinforced foam metal framework-based composite material
CN116855789A
In-situ synthesized graphene reinforced copper-based composite material and preparation method thereof
CN119101819A
Method for preparing graphene-reinforced titanium-based nanocomposite material via titanium hydride
WO2017070983A1
Cited By
Preparation method of graphene coated copper powder
CN120940641A
High-conductivity aerogel powder as well as preparation method and application thereof
CN121406017A
Polysaccharide coated-hydrogen pre-sintered dispersed graphene copper composite material and preparation method thereof
CN121797964A